2014
DOI: 10.1090/s0002-9947-2014-06256-9
|View full text |Cite
|
Sign up to set email alerts
|

The 𝐬-Eulerian polynomials have only real roots

Abstract: We study the roots of generalized Eulerian polynomials via a novel approach. We interpret Eulerian polynomials as the generating polynomials of a statistic over inversion sequences. Inversion sequences (also known as Lehmer codes or subexcedant functions) were recently generalized by Savage and Schuster, to arbitrary sequences s of positive integers, which they called s-inversion sequences.Our object of study is the generating polynomial of the ascent statistic over the set of s-inversion sequences of length n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(119 citation statements)
references
References 33 publications
2
117
0
Order By: Relevance
“…In particular, they show that h * (O(P, s); z) can be expressed as a sum of related polynomials which are an interlacing sequence. We should note that this is similar to the method used by Savage and Visontai [35] to prove Theorem 4.2. The reader should consult [7] for background and details on this method of proving real-rootedness.…”
Section: Results: Lecture Hall Order Polytopesmentioning
confidence: 71%
See 1 more Smart Citation
“…In particular, they show that h * (O(P, s); z) can be expressed as a sum of related polynomials which are an interlacing sequence. We should note that this is similar to the method used by Savage and Visontai [35] to prove Theorem 4.2. The reader should consult [7] for background and details on this method of proving real-rootedness.…”
Section: Results: Lecture Hall Order Polytopesmentioning
confidence: 71%
“…The s-Eulerian polynomials also possess many of the same nice properties of Eulerian polynomials, namely unimodality and real-rootedness due to the following theorem of Savage and Visontai [35]. The proof of this theorem uses the idea of compatible polynomials and interlacing to prove real-rootedness.…”
Section: Results: Lecture Hall Simplicesmentioning
confidence: 99%
“…Savage and Visontai [14,Conjecture 3.25] further conjectured the following equidistribution, which was proved very recently (and independently) by Chen et al [4] using type B P -Partitions. t des(π) = 1 + 31t + 55t 2 + 9t 3 = e∈I (1,4,3,8) 4 t asc(e) .…”
Section: Zhicong Linmentioning
confidence: 87%
“…They additionally showed that they contain the local h-polynomials for some well-studied subdivisions of simplices which are closely related to derangement polynomials. The h * -polynomials of the s-lecture hall simplices, called the s-Eulerian polynomials, were shown to be real-rooted and unimodal in [21]. The results of [16] then suggest that these nice properties of the h * -polynomial of a simplex can be inherited by its local h * -polynomial.…”
Section: Some Weighted Projective Spacesmentioning
confidence: 98%
“…The simplices ∆ ! n and P s n are both reflexive (see [23] for the definition of reflexive) with h * -polynomial A n+1 (z), and the combinatorics of both are intimately tied to the combinatorics of inversion sequences [21,23]. Despite this, the distinction in their local h * -polynomials further highlights that they exhibit fundamentally different geometry and combinatorics.…”
Section: The Factoradic Simplexmentioning
confidence: 99%